Repeated Bout Effect in Muscle-Specific Exercise Variations. Issue 8 (August 2015) - Zourdos, Michael C.; Henning, Paul C.; Jo, Edward; Khamoui, Andy V.; Lee, Sang-Rok; Park, Young-Min; Naimo, Marshall; Panton, Lynn B.; Nosaka, Kazunori; Kim, Jeong-Su
Abstract : Abstract: Zourdos, MC, Henning, PC, Jo, E, Khamoui, AV, Lee, S-R, Park, Y-M, Naimo, M, Panton, LB, Nosaka, K, and Kim, J-S. Repeated bout effect in muscle-specific exercise variations. J Strength Cond Res 29(8): 2270–2276, 2015—A single bout of unaccustomed exercise confers protective effect against muscle damage from a subsequent bout of similar activity, that is, repeated bout effect (RBE). It remains unknown whether varying muscle-specific exercise between sessions alters the magnitude of the RBE. This study examined the effects of muscle-specific exercise variation between consecutive sessions on the RBE. Twenty untrained males (21 ± 2 years) were assigned to one of 2 groups ( n = 10 per group): (a) 2 sessions of incline curls, Fixed Exercise or (b) 1 session of incline curls followed by 1 session of preacher curls, Varied Exercise, with 7 days between sessions. Subjects performed 5 sets of 6 repetitions at ∼50% of maximal isometric elbow flexor strength during each session. Changes in maximal voluntary isometric and isokinetic torque, range of motion, muscle soreness, and serum creatine kinase were measured before, immediately after, and 24, 48, 72, and 96 hours after each exercise session, and the changes were compared between bouts and between groups. There were significant time effects ( p < 0.05) for isometric maximal voluntary contraction, concentric maximal voluntary contraction, range of motion, and muscle soreness during sessions 1 and 2 with no between-group differences. Both groups demonstrated a significantly faster recovery of range of motion and soreness to baseline levels after session 2 compared with session 1. Overall, our findings suggest that incline curls conferred a protective effect during subsequent preacher curls in a similar way to repeating incline curls; therefore, the RBE was not exercise specific.